Developing the influence of discipline and work motivation on the performance of educators in the student guidance section - Hesri Mintawati; Asep Hikmat; Kohar Pradesa; Idha Gusmara (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose of this study was to determine how much influence discipline and work motivation have on teacher performance. The population in this study were 78 teachers at Setukpa Lemdikpol Sukabumi who worked in the student guidance section. The sample size of this study is the same as the population size using the Saturated Sampling Technique. Survey method was used for this research, and questionnaire was the research tool. Simple regression analysis, multiple regression analysis, and simple and multiple correlation analysis were the ways to look at the data. Before testing the proposed hypothesis, an analysis requirement test was conducted. The results of descriptive analysis show that the performance, work discipline, and work motivation of teaching staff are in the high category. While the results of hypothesis testing show: There is a significant positive effect of work discipline on the performance of educators in the student development section of Setukpa Lemdikpol Sukabumi; Work motivation affects the performance of educators in the student development section of Setukpa Lemdikpol Sukabumi. This effect is significant and positive; and There is a significant positive effect of educators' work discipline and work motivation on the performance of educators in the student development section of Setukpa Lemdikpol Sukabumi.